2018
DOI: 10.1136/bcr-2018-225018
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising fasciitis as a complication of primary varicella infection in an immunocompetent child

Abstract: Necrotising fasciitis (NF) is an infrequent yet significant complication of primary varicella infection in immunocompetent children. We report a case of a 4-year-old girl who presented three days into her chicken pox illness, with a rapidly progressing, severely tender erythematous rash surrounding one chicken pox lesion on her thigh. She required intravenous antibiotics, two surgical debridements, a skin graft and a prolonged stay in the paediatric intensive care unit, but ultimately we were able to save her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…24 By far, the most frequent manifestation of these superinfections is cellulitis, but cases have been reported of myositis, septic arthritis, craniofacial abscesses, and NF. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]25 NF as a sequela of chickenpox is well described in the medical literature. A systematic review of all reported NF cases in children identified 324 cases, with an association to VZV identified in 100 of them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 By far, the most frequent manifestation of these superinfections is cellulitis, but cases have been reported of myositis, septic arthritis, craniofacial abscesses, and NF. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]25 NF as a sequela of chickenpox is well described in the medical literature. A systematic review of all reported NF cases in children identified 324 cases, with an association to VZV identified in 100 of them.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with the delay of 3 to 5 days most commonly reported in the literature. 10,12,[15][16][17][18][19][20] Parents noted that this was preceded by high fever, whereas the initial chickenpox symptoms presented with mild or absent fever. We suggest that parents should be informed that new high temperatures, particularly if an initial mild fever has already resolved, should warrant extra vigilance for signs of soft tissue infection and a lower threshold to seek medical attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation